The redistributive effect and progressivity of taxes revisited: An international comparison across the European Union - Gerlinde Verbist; Francesco Figari (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Over the last few years concern for income inequality in European countries has increased remarkably. In this context, taxation is an important redistributive instrument and we investigate the redistributive role of direct taxes. We focus on the EU-15 countries and the evolution over the period 1998-2008, using EUROMOD, the EU-wide tax-benefit model. The research aim of this paper is twofold. First, we investigate empirically whether there is a link between pre-tax income inequality and redistribution through taxes. Second we hereby test whether there is a relationship between progressivity and the average tax level, the two building stones of the redistributive impact of taxes.
Keywords: C81; D31; H23; H24; 330; income redistribution; income taxes; social insurance contributions; microsimulation; European Union; EUROMOD